Evolution of the Brazilian residential carbon footprint based on direct energy consumption - Sanches-Pereira, Alessandro; Tudeschini, L.G.; Coelho, S.T. (PERGAMON-ELSEVIER SCIENCE LTD, 2016)
As one of the leading nations on climate negotiations, Brazil has to go beyond its voluntary commitment to reduce its carbon footprint and become a more constructive and less low-key player in the UNFCCC negotiations. In this context, the studys main objective was to evaluate the Brazilian residential energy consumption, its regional specificity, and the related carbon emissions. The results show that the poor coming out of poverty affects the size of the increase in energy demand. Especially in the case of carbon emission from direct energy consumption for cooking, in which as the poor come out of poverty their demand for high efficiency energy carriers increases leading to lower emissions or vice versa. Also, the results show that the country must ratifies its commitments to the global efforts to combat climate change not only by elaborating but also by conducting more ambitious initiatives to reduce carbon emissions from its own territory.